Geothermal conceptual and numerical modelling of a gas-condensate field in the Eastern Llanos Basin, Colombia - Andrés Felipe Laverde Martínez 1999- (2022)
Thesis of 60 ECTS credits submitted to the School of Science and Engineering at Reykjavík University in partial fulfillment of the requirements for the degree of Master of Science (M.Sc.) in Sustainable Energy Science This project presents three-dimensional conceptual and numerical flow models of a gas-condensate field in the foothills region of the Eastern Llanos Basin in Colombia. The Eastern Llanos Basin has been the subject of diverse studies for hydrocarbon exploitation. Over the past decade, this region has been assessed for its geothermal potential in currently exploited oil & gas fields. A gas-condensate field located in the foothills of the basin represents a promising opportunity to produce geothermal energy. The conceptual and numerical models integrate geological, geophysical, geochemical and well data to enhance the understanding of the geothermal system in a sedimentary environment. The Leapfrog Geothermal model shows that the gas-condensate field presents a structurally complex architecture, where hydrocarbons and water accumulate in a relatively permeable reservoir. Well data exhibit a constant geothermal gradient, indicating conductive heat transfer. Based on geochemical data and hydrological analyses, it is identified that meteoric recharge occurs in the Andean orogenic belt and fluid flows -from NW to SE. TOUGH2 numerical simulations are developed to generate a natural state model and geothermal production scenarios, which give an estimation of water extraction in the field. The thermal and hydraulic parameters were extracted from published experimental and well data. In order to simplify this first geothermal model, and reduce the number of parameters, it is assumed that the field is completely saturated with water. The natural state model temperature field is concordant with measured well data and simulated mass flow direction confirms expected patterns. Production scenarios demonstrate that it is possible to extract water at more than 90 °C without thermal breakthrough during the 30 ...